Komparasi Daya Saing dan Determinan Ekspor Produk Turunan Batubara Indonesia-Australia ke Pasar Asia - Dwike Handaru Ulia; Wiwiek Rindayati (Institut Nurul Islam Mojokerto, 2025)
Coal is one of the leading export commodities for Indonesia and Australia. Both countries, as one of the world's largest coal producers and exporters, are now focusing on exporting processed coal such as bituminous coal (HS 270112) to improve competitiveness. The methods used include Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), X-model, and panel data regression. The RCA results show that Indonesian and Australian coal-derived products are highly competitive in ten Asian countries. EPD reveals Indonesia's position in China and Hong Kong is in the rising star position. While Australia is in a rising star position in Hong Kong, India, Japan, and Vietnam. X-model shows optimistic market prospects for Australia in five countries and Indonesia in two Asian countries. Panel data regression shows that GDP per capita, RCA, and export prices have a positive and significant effect, while inflation, REER, and covid-19 dummy have a negative and significant effect. The LPI variable has no significant effect on the export value of coal-derived products.